The Effect of Small Side Games Training on Passing Skills in Futsal Games at Kayumanis 1 Elementary School, Bogor City - Rabbani, Naufal; Dinangsit, Dinar; Saptani, Entan (UNIVERSITAS NEGERI MAKASSAR, 2025)
Weaknesses and mistakes in passing are found in the weight of the pass or the strength of the pass which is still poor or weak, the accuracy of the pass or the precision of the pass, the view (head up), foot support, contact with the ball, foot position, and so on. The training model used in futsal passing training is a monotonous training model facing each other when carrying out the training. This research aims to analyze the effect of small-sided games training on passing skills in futsal extracurricular students at Kayumanis I Kota Bogor Elementary School. The method used in this research is experimental, while the research design used is pre-test-post test one group design. The population in this study were active members of extracurricular futsal students at Kayumanis I Kota Bogor Elementary School with a total population of 20 students from the total sample. The data collection technique uses test passing. To analyze the data using the Kolmogorov Smirnov Test, and homogeneity testing with the t-test using SPSS 26.